Life quality of students majoring in sports education and its comparison with other students - Yudy Hendrayana; Yusuf Hidayat; Dini Tresnadiani; Burhan Hambali (Jurnal Cakrawala Pendidikan, 2022)
Since it encompasses all facets of life, including health, hope, job, family, environment, and other aspects of daily existence, quality of life is one of the most important factors that may be categorized as a multidimensional term. However, each person's living circumstances might undoubtedly vary, which has an impact on how they perceive their quality of life. This study uses a descriptive survey method to investigate how students who undergo sports education and those who don't see their quality of life differently. It involved purposively selected 245 sports education students and 135 non-sports education students registered as active students admitted in the academic year of 2016-2019 in five (5) universities in Indonesia. All data, collected by using the WHOQOL-BREF quality of life scale, were quantitatively analyzed through the independent sample t-test. The results of the analysis likely prove that, in general, most students perceive a relatively good quality of life though there are differences in the quality of life between both groups. Students majoring in sports, however, have a better perception of quality of life than do non-sports education learners.